2021
DOI: 10.1186/s12893-021-01411-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous cholecystostomy as a definitive treatment for moderate and severe acute acalculous cholecystitis: a retrospective observational study

Abstract: Background In this study, we aimed to investigate risk factors for the relapse of moderate and severe acute acalculous cholecystitis (AAC) patients after initial percutaneous cholecystostomy (PC) and to identify the predictors of patient outcomes when choosing PC as a definitive treatment for AAC. Materials and methods The study population comprised 44 patients (median age 76 years; range 31–94 years) with moderate or severe AAC who underwent PC wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…PC in high-surgical-risk patients with AC could be a definitive treatment [16,17]. The limitations of this study include its retrospective design and some factors or variables that may not be investigated that were the reasons for the difference in outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…PC in high-surgical-risk patients with AC could be a definitive treatment [16,17]. The limitations of this study include its retrospective design and some factors or variables that may not be investigated that were the reasons for the difference in outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies in the past have highlighted the importance of PC in high-risk and frail patients, presenting it as the only effective treatment for settling acute or recurrent AC attacks in that population [ 20 ]. However, there has been a rise in using PC to manage even younger patients with severe attacks of AC, and its use is gaining more acceptance [ 21 ]. Additionally, a large American group study also concluded that PC provided superior results in managing severe attacks of AC in comorbid patients.…”
Section: Discussionmentioning
confidence: 99%
“…The electronic medical database of our institution was searched for records of 316 AC patients who underwent PC for the first time between January 1, 2017, and June 30, 2021. The diagnosis of AC was based on clinical symptoms and signs (fever, abdominal pain, positive sonographic Murphy’s sign, or elevated inflammatory markers, such as white blood cells) and radiologic studies by abdominal US (ultrasonography), CT and so on [ 11 ]. Patients with concurrent or secondary pancreatitis (n = 41) and pancreatic trauma (n = 1) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The gallbladder contents were aspirated via a 10-mL needle. Then, a 0.035-inch guidewire was inserted, followed by placement of an 8-Fr pigtail catheter [ 11 ]. The characteristics of the bile were observed during PC.…”
Section: Methodsmentioning
confidence: 99%